Sistem Penunjang Keputusan dengan Metode Simple Additive Weighting (SAW) untuk Pemilihan Bahan Baku Kayu Berkualitas pada Produksi Perabot - Maulana, Halim; Suryana, Febriyanno; Gusrion, Deval; Efendi, Raimon (Innovative: Journal Of Social Science Research, 2025)
Hafiz Perabot faces challenges every year in selecting quality wood raw materials for the production process. This selection process is still done manually, so the decisions made are less precise, take a long time, and are inefficient. To improve production efficiency and ensure the use of quality raw materials, a more optimized system is needed. The solution to overcome this problem is to implement a web-based Decision Support System (SPK) using the Simple Additive Weighting (SAW) method. This method calculates the weighted sum to produce rankings as a basis for decision making in the selection of quality wood raw materials. The application was developed using the PHP programming language with a MySQL database for fast and accurate data management. The results of this study indicate that there is 1 quality wood raw material received from 10 wood material data, namely V8 (Ulin) with Rank 1. This Decision Support System can help Hafiz Perabot in determining quality wood raw materials, thereby improving production quality and efficiency in the decision-making process.